Planning the Development of a Daily Parental Journal to Stimulate Religious and Language Development in Early Childhood - Nurrizalia, Mega; Shomedran, Shomedran; Fitriana, Fitriana; Septiyanda, Dwi (Universitas Negeri Padang, 2025)
The development of religious and language values in early childhood requires proper stimulation from parents as the primary educators. However, many parents face difficulties in planning and implementing stimulation activities consistently, especially after the pandemic, many early childhood children experience delays in the development of religious and language values. This study explores the need to develop parent daily journal materials to support the stimulation of children's religious and language value development, identify factors of parental involvement, and evaluate the role of daily journals in overcoming post-pandemic problems. This study used a mixed method with an exploratory sequential design. Data were collected through in-depth interviews, closed questionnaires, and participatory observations from 30 parents in Palembang City. The results showed that 86.67% of parents felt that journals made it easier to record development, 73.33% were helped in stimulation, and 76.67% experienced increased knowledge. However, 93.33% of parents were still confused about choosing the right activities. So that development was carried out on the material for stimulating activities for the development of religious and language values in early childhood through fun activities at home. This study highlights the importance of practical tools to support informal education at home.